2016
DOI: 10.1111/lam.12538
|View full text |Cite
|
Sign up to set email alerts
|

The role of reactive oxygen species in the antibacterial photodynamic treatment: photoinactivationvsproliferation

Abstract: The main purpose in antibacterial photodynamic therapy (PDT) is to kill the micro-organisms that cannot be destroyed by conventional methods. Low-level light and/or low concentration of reactive oxygen species may trigger some biochemical pathways that lead to cell proliferation. Thus, there is a risk of bacterial cell proliferation during PDT. In this study we report that PDT with ICG application can induce biostimulation when laser dose and photosensitizer concentration are not optimized properly. Therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 30 publications
0
14
0
2
Order By: Relevance
“…Our results obtained with VIS+wIRA on planktonic bacteria showed the antimicrobial effect was dependent on the ICG concentration used. Topaloglu et al [68,69] reported on the risk that lower ICG concentrations used during aPDT cannot only eliminate bacteria but actually increase the proliferation rate of bacteria, as demonstrated in in vitro experiments with P. aeruginosa [29]. This was explained by the amount of ROS, which was generated and determined the actual level of bactericidal effect or proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Our results obtained with VIS+wIRA on planktonic bacteria showed the antimicrobial effect was dependent on the ICG concentration used. Topaloglu et al [68,69] reported on the risk that lower ICG concentrations used during aPDT cannot only eliminate bacteria but actually increase the proliferation rate of bacteria, as demonstrated in in vitro experiments with P. aeruginosa [29]. This was explained by the amount of ROS, which was generated and determined the actual level of bactericidal effect or proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…The main working mechanism is the absorption of light energy by the photoreceptors located in the cell membrane or the chromophores in the mitochondria, particularly cytochrome c oxidase (CCO) which is a component of the mitochondrial respiratory chain 13 . Thus, it may induce biostimulation with many consecutive biochemical reactions that result in cell proliferation, migration, adhesion, and apoptosis 14,15 . There are several signaling cascades in eukaryotic cells and low‐level light therapy has to potential to induce these cascades resulting in proliferation and migration.…”
Section: Introductionmentioning
confidence: 99%
“…13 Thus, it may induce biostimulation with many consecutive biochemical reactions that result in cell proliferation, migration, adhesion, and apoptosis. 14,15 There are several signaling cascades in eukaryotic cells and low-level light therapy has to potential to induce these cascades resulting in proliferation and migration. According to the previous reports, it was declared that low power light may stimulate the phosphorylation of tyrosine-protein kinase receptors (TPKR).…”
mentioning
confidence: 99%
“…The European Research Journal 2021 μM Ce6 caused nearly 50% reduction in cell viability which can be considered as a high dark toxicity and this cannot support idea of aPDT with less side effect in neighboring areas of biological tissues [23].…”
Section: Discussionmentioning
confidence: 94%